Identifikasi Risiko Lanjutan Terhadap Sumber dan Penyebab Material Waste Proyek Konstruksi Jalan - Waty, Mega; Sulistio, Hendrik (Department of Civil Engineering, Diponegoro University, 2020)
Early risk identification of the sources and causes of waste material for road construction projects has been carried out, and the research continues to carry out further risk identification which then becomes the final risk identification. Description and validity tests and reliability tests were carried out to obtain further risk identification. Each source variable and indicator of the cause of material waste in each material is differentfrom one another because each has a difference. The results of continued identification resulted in: 1) ready mix concrete has eight variables of waste material sources and 21 indicators of material waste causes, 2) lean concrete has seven variables of waste material sources and 18 indicators of material waste causes, 3) aggregate B has seven variables of waste material sources and 12 indicators of material waste causes, 4) landfill has eight variables of material waste sources and 26 indicators of material waste causes, 5) cement has seven variables of material waste sources and 31 indicators of material waste.